Predicting Risk for Comorbid Reading and Mathematics Disability Using Fluency‐Based Screening Assessments. Issue 2 (1st May 2022) - Martin, BrittanyLee N.; Fuchs, Lynn S.
Abstract: The first purpose of this study was to examine the prevalence of risk for comorbid reading and mathematics disabilities (RMD) at start of first grade, when measured in a representative sample of 3, 062 students with first‐grade fluency measures (word reading; computation). The second purpose was to examine the utility of these measures for predicting RMD status within a sample of 577 students when RMD status was assessed at the end of second grade in terms of reading and math accuracy. When set at or below the 16th percentile, first‐grade risk for RMD was two times more common than chance; at or below the 7th percentile, it was five times more common. Logistic regression showed that the two first‐grade fluency measures accurately distinguished students with and without RMD in second grade; however, when cut scores were set to capture 85% of students with RMD, false positives were high. Overall, the results provide support for the use of fluency measures as an initial gating procedure in first grade, but additional gating steps appear necessary in the screening process to reduce false positives.